Comparison of Mandarin tone and speech perception between advanced combination encoder and continuous interleaved sampling speech-processing strategies in children. - Hwang CF; Chen HC; Yang CH; Peng JP; Weng CH (American Journal of Otolaryngology, 2012)
Abstract: Objective: This study was performed to compare cochlear implant (CI) users'' performance in Mandarin speech and tone perception between 2 types of speech-processing strategies—advanced combination encoder (ACE) and continuous interleaved sampling (CIS)—under quiet and noisy conditions. Methods: This study involved 10 congenitally deaf children (age range, 5.7–15.3 years; mean, 9.2 years) who received the Nucleus 24-channel CI system cochlear device (CI24R; Cochlear Ltd, Lane Cove NSW, Australia). The subjects used ACE since switching on their CI devices. Speech and tone perception tests were administered under quiet and noisy (+5 dB signal-to-noise ratio) conditions with ACE and CIS strategies 20 minutes and 2 weeks apart. Results: Regardless of the strategy used, subjects showed significantly higher scores in speech perception than in tone recognition. Under noisy conditions, subjects had significantly higher tone identification scores with the CIS than the ACE strategy (P = .038). There was no significant difference in speech identification score between the strategies. Subjects showed significant higher tone identification and speech perception scores under quiet than noisy (+5 dB signal-to-noise ratio) conditions. Subjectively, 6 subjects preferred the ACE strategy, and the remaining 4 preferred the CIS strategy. The strategy preference of the subjects was related to speech perception performance rather than tone identification. A significant correlation was observed between tone identification and speech recognition, regardless of whether speech was evaluated by consonants (r = 0.669, P < .001), vowels (r = 0.426, P = .001), or sentences (r = 0.294, P = .023). Conclusion: There are only 4 patterns of tone in Mandarin, which is far fewer than the number of speech sounds. However, tone identification is poorer than speech perception. The CIS speech-processing strategy may improve tone identification under noisy conditions. Before improved speech strategies to code acoustic characteristics of tone can be developed, it would be worthwhile to try both CIS and ACE for CI users and to select the most suitable speech-processing strategy according to the subjective preference and objective performance.